2017
DOI: 10.1002/biot.201700114
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Based Production of Dimethyl Itaconate From Rice Wine Waste‐Derived Itaconic Acid

Abstract: Dimethyl itaconate is an important raw material for copolymerization, but it is not synthesized from itaconic acid by organisms. Moreover, Corynebacterium glutamicum is used as an important industrial host for the production of organic acids, but it does not metabolize itaconic acid. Therefore, the biosynthetic route toward dimethyl itaconate from itaconic acid is highly needed. In this study, a biological procedure for dimethyl itaconate production is developed from rice wine waste-derived itaconic acid using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Lipases have been reported to preferentially catalyze reactions in organic solvents or at the oil–water interface; they hardly catalyze reactions in the aqueous phase . Thus far, the use of lipases in catalyzing the esterification of IA has received very little attention; only one study has reported the lipase-catalyzed esterification of IA in the aqueous phase, in which the DI yield was only 55.3% . In this study, a higher DI yield was realized.…”
Section: Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Lipases have been reported to preferentially catalyze reactions in organic solvents or at the oil–water interface; they hardly catalyze reactions in the aqueous phase . Thus far, the use of lipases in catalyzing the esterification of IA has received very little attention; only one study has reported the lipase-catalyzed esterification of IA in the aqueous phase, in which the DI yield was only 55.3% . In this study, a higher DI yield was realized.…”
Section: Results and Discussionmentioning
confidence: 64%
“…Most lipases have poor tolerance to methanol; thus, using water is a better option because water is not only a good solvent for IA but also provides a friendly environment for lipases. In 2017, Joo et al carried out the first trial on the biobased production of DI from rice wine waste-derived IA in aqueous media using Rhizomucor miehei lipase and methanol substrate and achieved the DI yield of only 55.3% …”
Section: Introductionmentioning
confidence: 99%
“…Recently, metabolically engineered C. glutamicum was grown on alternative carbon sources like xylose 1517 to produce industrially relevant chemicals. 4,18,19 Previously, ethylene glycol (3.5 g/L) has been produced from glucose at a yield of 0.25 mol/mol (or 0.10 g/g) via the serine biosynthetic pathway using engineered C. glutamicum . 20 In addition, 5.3 g/L glycolate (a yield of 0.18 g/g [0.43 mol/mol]), from a mixture of glucose and acetate, has been produced in engineered C. glutamicum .…”
Section: Introductionmentioning
confidence: 99%
“…inaquosorum CSB31," [6] the authors screen for a mannanase producer. An extreme alkaline mannanase (MnB31) enzyme was then purified and the biochemical and thermodynamic properties were examined for utilization in various biotechnological processes using different substrates.Moreover, a Research article on the "Bio-based production of dimethyl itaconate from rice wine waste-derived itaconic acid," [7] shows the potential for bio-based production of raw materials for copolymerization from renewable carbon sources. The authors demonstrate that dimethyl itaconate can be produced by engineered C. glutamicum, starting from itaconic acid produced from rice wine waste-derived carbohydrates.…”
mentioning
confidence: 99%
“…Moreover, a Research article on the “Bio‐based production of dimethyl itaconate from rice wine waste‐derived itaconic acid,” shows the potential for bio‐based production of raw materials for copolymerization from renewable carbon sources. The authors demonstrate that dimethyl itaconate can be produced by engineered C. glutamicum, starting from itaconic acid produced from rice wine waste‐derived carbohydrates.…”
mentioning
confidence: 99%